A Rare Case of Primary Anterior Mediastinal Yolk Sac Tumor in an Elderly Adult Male - Sammy G. Nakhla; Srinath Sundararajan (Case Reports in Oncological Medicine)
Mediastinal germ cell tumors are extragonadal germ cell tumors (EGGCTs) commonly seen in children and young adults. They are more common in men. Clinically they are classified as teratomas, seminomas, and nonseminomatous germ cell tumors. Primary mediastinal yolk sac neoplasm is an extremely rare tumor. We present here a very rare case of primary yolk sac tumor of the anterior mediastinum in a 73-year-old male. Mediastinal germ cell tumors have a worse prognosis than gonadal germ cell tumors. Chemotherapy followed by adjuvant surgery improves overall response in EGGCTs. However, comorbidities can render treatment with chemotherapy and surgery challenging in elderly patients.